FAO/IBPGR technical guidelines for the safe movement of vanilla germplasm - Pearson, M.N.; Jackson, G.V.H.; Zettler, F.W.; Frison, Emile A.; Food and Agriculture Organization of the United Nations; International Board for Plant Genetic Resources (1991)
These guidelines are divided into 2 parts. The first makes general and technical recommendations on how best to move Vanilla germplasm and mentions institutions recovering and/or maintaing pathogen-tested material. The second part covers the important virus diseases of quarantine concern. The information given on any particular pest or pathogen concentrates on those aspects most relevant to quarantine. (Abstract © CAB ABSTRACTS, CAB International)